Seismic performance of precast shear wall of insufficient grouting material strength strengthened with steel plate. (November 2022) - Gu, Sheng; Han, Ruiqing; Li, Shengli; Wu, Guangming; Zhang, Jiwen
Abstract: The sleeve-connected precast shear wall is used widely in engineering practice due to its high engineering quality and environmental protection. However, the insufficient grouting material strength due to negligent management affects greatly the mechanical properties of the precast shear walls. Three different strengthening methods of steel plate were proposed, and the seismic performance of the shear walls was studied under the horizontal low-cycle repeated loading. Results demonstrated that the extension of the cracks of the shear walls strengthened with steel plate was limited effectively and the damage degree was reduced significantly. The failure characteristic of the first crack in the shear walls was revealed. The peak load of the specimen with insufficient grouting material strength (CPSW) was 80.05% of the specimen with normal grouting material strength (NPSW). The cracking and peak loads of specimens strengthened with different methods (CPSW-R1, CPSW-R2, and CPSW-R3) were improved significantly, and the ductility of shear walls was 108.9%, 102.7%, and 100.7% of the specimen NPSW, respectively. The stiffness and energy dissipation capacity of the shear walls strengthened were restored to the level of the specimen NPSW. The results of this paper could provide some insight into the strengthening and maintenance of shear walls with insufficient grouting material strength.